ANALISIS KESESUAIAN INSTRUMEN EVALUASI DALAM BUKU TEKS BAHASA INDONESIA SMA KELAS X DENGAN PERKEMBANGAN KOGNITIF SISWA - Yeni Yeni Witdianti (Department of Indonesian Language Education, Graduate School, University of Muhammadiyah Prof. DR. HAMKA, 2022)
This article is a descriptive study that aims to determine the suitability of the evaluation instrument for the class X Indonesian language textbook evaluation, published by Tiga Serangkai, with the cognitive development of students. The object of this research is an evaluation instrument in the form of an essay test (description) contained in the Indonesian language textbook (BTBI) class X SMA totaling 60 items. The analysis technique used is the observation procedure, namely (1) identifying the object of research, (2) explaining the various types of data that have been collected, and (3) discussing the research data. The identification of the research object is done by coding various data on indicators of student cognitive development, namely by examining the operational words used and the form of bills or competencies to be measured. The results of data collection in this study were analyzed using descriptive analysis with percentage data. Based on the analysis of 3 characteristics of students' cognitive development on the 60 item descriptions obtained 41, 67% abstract thinking, 20% systematic thinking ability, and 38, 33% experimental thinking ability. Thus it can be concluded that the evaluation instrument in the Indonesian textbook for SMA class X, published by Tiga Serangkai, is in accordance with the cognitive development of the students.